Fluids for youth athletes - Lambert, M.; Malinauskas, B. M. (Virginia Journal, 2005)
From late spring to early fall, hot and humid weather is common, which makes staying properly hydrated increasingly important. As compared to adult athletes, youth athletes sweat less, produce more heat, and are less able to transfer heat from muscles to skin while exercising. Additionally, children have a greater ratio of surface area to body volume as compared to adults, and therefore are exposed to a faster influx of heat when environmental temperature exceeds skin temperature. Thus, youth athletes are at especially high risk for exercise-induced dehydration. The following reviews characteristics of dehydration and provides guidance to promote proper hydration for the youth athlete.